The Search for Biomarkers in Alzheimer's Disease - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: As population demographic shift and the number of individuals with Alzheimer Disease (AD) continue to increase, the challenge is to develop targeted, effective treatments and our ability to recognize early symptoms. In view of this, the need for specific AD biomarker is crucial.CONTENT: In recent years it has become evident that CSF concentrations of some brain-specific proteins are related to underlying disease pathogenesis and may therefore aid clinical investigation. Among several, we have focused on three candidates that have been suggested to fulfil the requirements for biomarkers of AD: β-amyloid 42 (Aβ42), total Tau (T-tau) and tau phosphorylated at various epitopes (P-tau). An increasing number of studies suggest that supplementary use of these CSF markers, preferably in combination, adds to the accuracy of an AD diagnosis. More recently visinin – like protein (VLP-1), a marker for neuronal cell injury has been studied. CSF VLP-1 concentrations were 50% higher in AD patients than in the control population.SUMMARY: The number of studies aimed at the identification of new biomarkers for AD is expected to increase rapidly, not only because of the increasing insights into the pathological mechanisms underlying this disease, but also because new therapies have been developed or are under consideration now, which warrant an early and specific diagnosis for effective treatment of the patients.KEYWORDS: dementia, amyloid plaque, neurofibrillary tangels, amyloid β-peptide 42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau), visinin–like protein 1 (VLP-1)